Status of Gobiosoma (Teleostei: Gobiidae) from Brazil: description of a new species, redescription of G. hemigymnum, molecular phylogeny of the genus, and key to Atlantic species - Tassell, James L. Van; Joyeux, Jean-Christophe; Macieira, Raphael Mariano; Tornabene, Luke (Zootaxa, 2015)
It is unclear how many species of Gobiosoma occur in Brazil and what their geographic distributions are. Here we combine data from a comprehensive morphological survey and a molecular analysis to clarify this uncertain taxonomy and place Brazilian Gobiosoma within a phylogenetic framework. Recent collections in Brazil, from the states of Ceará to Santa Catarina, and in Uruguay yielded two allopatric species of Gobiosoma that are distinct in genetics, meristics, morphometrics, scale pattern and coloration. Comparisons were made with types and specimens of Gobiosoma hemigymnum, Garmannia mediocricula, Gobiosoma spilotum and Gobiosoma parri and all other known species of Gobiosoma. We place G. parri in synonomy with G. hemigymnum with a distribution of Rio de Janeiro to Uruguay and Argentina. The northern species, that extends from the states of Espírito Santo to Ceará, is described as a new species, Gobiosoma alfiei. A key to the Atlantic species of Gobiosoma is provided.